"A Definitive but Unsatisfying Answer": The Evangelical Response to Gay Christians. Issue 1 (2022) - Neumann, David J.
ABSTRACT: As an amorphous, nonhierarchical collection of associations, evangelicalism has always lacked a clear source of authority. Since Christianity Today's beginning in 1956, it has aspired to serve as the mouthpiece of authoritative evangelical views, presenting itself as the voice of moderation while espousing conservative views with a combative, culture-war stance. With the emergence of the gay rights movement, evangelicals launched a culture war against "homosexuals" as the implicitly secular, liberal Other and then were forced to wrestle with how to apply this stance toward their gay Christian brothers and sisters. Evangelicals' self-conception led to a contradictory stance that they managed to maintain with little variation for decades. Committed to biblical inerrancy, they were definitive in condemning gay sexual behavior, but as self-identified postfundamentalists, they also desired to be compassionate toward gay people. They encouraged gay Christians to change their sexual orientation and simultaneously admitted that such change was impossible for most. Though evangelicals were slow to welcome the ex-gay movement, they eventually embraced it fully as the only plausible escape from their contradictory ideology. The collapse of the movement thus came as a major blow. Many evangelicals began to question the premise that sexual orientation was a chosen, changeable identity and began to rethink the theology of inerrancy that undergirded evangelical hermeneutics. Since 2010, a number of evangelical leaders have challenged CT's claim to represent the evangelical consensus on the issue. In the coming years, the progressive views of younger evangelicals will undoubtedly increase acceptance of same-sex relationships.